Answer: T(x,y) = (x+4, y+3)
=============================================
When we apply the rule T1, we shift the point 3 units to the right as x+3 indicates. Then when T2 happens, we shift another 1 unit to the right due to the x+1. Overall, the point will shift 4 units to the right (3+1 = 4) after we apply T1 and then T2. The order of the translations doesn't matter. Therefore the x part of the rule is x+4
For the y shifts, T1 moves the point down 4 units and T2 moves the point up 7 units. The net of this is 3 units up because 7+(-4) = 3. Therefore the y portion will be y+3
Overall, we combine the two pieces to get this complete transformation: T(x,y) = (x+4, y+3) telling us to move the point 4 units to the right and 3 units up.